Effects of desertification on permafrost environment in Qinghai-Tibetan Plateau. (15th May 2020) - Chen, Lin; Yu, Wenbing; Han, Fenglei; Lu, Yan; Zhang, Tianqi
Abstract: Soil thermal state exerts an important role in soil physicochemical properties, nutrient content, soil carbon losses, and hydrological processes in cold regions. In the Qinghai-Tibet Plateau, desertification and aeolian sand accumulation greatly change the surface cover types and simultaneously alter the surface energy budget. However, the quantification of their impacts on the soil thermal state hasn't been studied methodically. Here, a laboratory experiment was conducted to investigate the impact of surface cover types, including bare surface, grass-coved surface, dry and wet (3%) aeolian sand-covered surface, on underlying soil thermal state. Our results demonstrate that there is a reciprocal relationship between environment change and permafrost degradation. The amount of heat entering the active layer was determined by the surface cover types and soil water content. Using the bare surface case as a reference, vegetation layer acted as a buffer to reduce the amount of heat propagation downwards the ground by 20% and to lower the near surface temperature by 0.7 °C. In contrast, dry aeolian sand acted as an insulation layer and warmed the ground by about 2 °C. Also, wet aeolian sand with high thermal conductivity facilitated the heat exchange with the atmosphere and warmed the ground about 1.5 °C. Our results have implications for thermal and hydrological processes in the atmosphere-ground-permafrost system and thermal stability of infrastructure under the effect of the desertification and aeolian sand accumulation. The hydrothermal interaction of desertification and permafrost needs to be quantified in the further study through long-term field observations and a fully-coupled water flow and heat transport model under a changing climate. Highlights: Heat transfer characteristic of the aeolian sand was investigated using experimental model. Surface cover types and soil properties determines the freezing and thawing processes. Desertification warms the ground and degrades the permafrost. Sand thickness affects the amount of the atmospheric heat entering the ground.